Lower extremity muscle activity during reactive balance differs between adults with chronic traumatic brain injury and controls - Cesar, Guilherme M.; Buster, Thad W.; Burnfield, Judith M. (Frontiers in Neurology, 2024)
Background Control of reactive balance is key to achieving safe independent walking and engagement in life activities. After traumatic brain injury (TBI), motor impairments and mobility challenges are persistent sequelae. To date, no studies have explored muscle activity of individuals with chronic TBI during a task that requires reactive control of balance. Objective To investigate lower extremity muscle activity during a reactive balance test performed by adults with chronic severe TBI and matched controls. We hypothesized that abnormal activity of lower extremity muscles would be related with poorer reactive balance performance. Also, we performed an exploratory analysis for those with TBI investigating the impact of unilateral versus bilateral lower extremity involvement in the control of reactive balance. Methods Ten adults with chronic severe TBI who were independent community ambulators and ten matched controls performed the computerized reactive balance test (Propriotest®) while lower extremity muscle activity was recorded. Electromyographic (EMG) activity was contrasted (Mann–Whitney U Test) between groups across each 10 s epoch of the 120 s test. Additionally, test scores were correlated (Spearman) with lower extremity composite EMG activity to distinguish muscle activity patterns related with reactive balance performance. Lastly, reactive balance test scores were correlated with reactive balance test scores and clinical functional measures only for the TBI group. Results Although the TBI group exhibited greater EMG activity across the entire test compared with the control group, significant differences were not observed. Greater composite EMG activity correlated significantly with poorer reactive balance performance across most of the 10 s windows of the test. Conclusion Greater muscle activity exhibited during the reactive balance test by individuals with chronic severe TBI compared to those without disabilities, particularly at small unexpected perturbations, highlights the greater physiologic effort required to control reactive balance even after independent ambulation is achieved.